2015
DOI: 10.18410/jebmh/2015/437
|View full text |Cite
|
Sign up to set email alerts
|

COMPARISON BETWEEN 0 . 5% BUPIVACAINE - DEXAMET HASONE COMBINATION & 0 . 5% BUPIVACAINE - CLONIDINE COMBINATION IN BRACHIAL PLEXUS BLOCKS BY SUPRACLAVICULAR APPROACH

Abstract: BACKGROUND: Brachial plexus blocks, alone or in combination with general anesthesia, has become one of the most important anesthesia techniques for surgeries in the upper limb. Prolongation of analgesia using perineural catheters are not yet popular, and we are in need for an adjuvant that can prolong the action of local anesthetics after single injection peripheral nerve blocks. Dexamethasone and clonidine are two commonly used adjuvants. This study was undertaken to compare the analgesic efficacy of dexameth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
0
0
1
Order By: Relevance
“…Our observations are in accordance with a similar study published in 2015 by Kishore et al [8,23], who compared the addition of dexamethasone in a dose of 8 mg (group D), clonidine in a dose of 1 mcg/kg (group C), and saline 2 mL (group S) with 15 mL of 0.5% bupivacaine in BPB by supraclavicular approach and observed that dexamethasone turned out to be a better adjuvant as compared to clonidine, as it significantly extend the analgesia duration, without any significant side effects.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our observations are in accordance with a similar study published in 2015 by Kishore et al [8,23], who compared the addition of dexamethasone in a dose of 8 mg (group D), clonidine in a dose of 1 mcg/kg (group C), and saline 2 mL (group S) with 15 mL of 0.5% bupivacaine in BPB by supraclavicular approach and observed that dexamethasone turned out to be a better adjuvant as compared to clonidine, as it significantly extend the analgesia duration, without any significant side effects.…”
Section: Discussionsupporting
confidence: 94%
“…The time of onset for sensory and motor blocks in group LD was similar to group LC and group L (p>0.05) in our study. Similar results were observed in several earlier published studies [7][8][9]. Dar et al [7] published a study that showed a significantly early onset of sensory and motor blocks in the dexamethasone group compared to the ropivacaine group (p<0.05).…”
Section: Discussionsupporting
confidence: 87%
“…Penambahan klonidin 1 mcg/kgBB ternyata cukup memberi efek perubahan pada diberikan atropin 0,6 mg intravena. 14 Klonidin dapat menyebabkan penurunan resistensi vaskular sistemik yang dimediasi secara sentral dan juga melalui reseptor α2, serta melalui peningkatan tonus vagal yang mengakibatkan penurunan tekanan arteri rerata dan laju detak jantung. Hal ini juga menyebabkan penurunan sekresi norepinefrin dari ujung saraf perifer sehingga mengurangi respons stres.…”
Section: Pembahasanunclassified